ANALISIS USAHATANI KELAPA SAWIT SWADAYA DI DESA SUNGAI SITOLANG KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU PROPINSI RIAU - Ahlul Nazar; Tibrani (DINAMIKA PERTANIAN, 2024)
This study aims to explore the characteristics of farmers and the profile of independent oil palm farming to assess the technology utilized in self-sustaining oil palm cultivation. Additionally, it examines the factors involved in palm oil production, including production costs, outputs, income, and efficiency specific to Sungai Sitolang Village. The research employs a survey method conducted from July 2020 to December 2020. Findings indicate: (1) The average age of the farmers is 45 years, with an education level averaging nine years. Farmers have approximately 11 years of farming experience, typically supporting two dependents, and each farmer tends to an average land area of 2 hectares. (2) Initial land cultivation technologies primarily consist of tractors; however, many oil palm farmers in Sungai Sitolang Village still rely on traditional manual techniques such as machetes and spraying tanks, demonstrating limited adoption of modern technology. (3) Factors affecting oil palm farming include an average application of TSP fertilizer at 203.49 kg/ha/year, KCl at 278.85 kg/ha/year, and UREA at 453.01 kg/ha/year. The average annual expenditure on fertilizers is Rp. 8,042,086, with pesticide costs averaging Rp. 401,744 per hectare per year. Labor inputs are measured at 3.10 HOK/ha for field labor and 11.47 HOK/ha for harvesting. Overall production averages 6,133 kg/ha/year. Fixed costs total Rp. 305,159, while variable costs amount to Rp. 9,900,462.96. Gross income per hectare is Rp. 10,426,100 per year, resulting in a net income of Rp. 220,478.09 per hectare annually. The efficiency value of oil palm farming is calculated at 1.02.